1999
DOI: 10.1038/sj.bjc.6690339
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of TGF-β receptors in human colorectal cancer: implications for cancer development

Abstract: SummaryMany colorectal cancer cells are resistant to the anti-proliferative effects of transforming growth factor-β (TGF-β). TGF-β also acts as paracrine factor from cancer cells on their mesenchymal cells. The aim of this study was to examine the expression of TGF-β and its receptors in human colorectal cancer tissue and determine any relationship with cancer growth. In situ hybridization and Northern blot hybridization detection of TGF-β 1 , type I and type II receptor mRNA and immunohistochemical staining o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 42 publications
3
41
2
1
Order By: Relevance
“…In colon and prostate cancer loss of T␤RI expression was associated with increased malignant potential (25,32,33). No comparable studies exist for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In colon and prostate cancer loss of T␤RI expression was associated with increased malignant potential (25,32,33). No comparable studies exist for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from genetic and/or epigenetic lesions in TGF-b receptors or TGF-b/Smad transducers that can contribute to TGF-b resistance in human cancers (Arai et al, 1998;Ko et al, 1998;Matsushita et al, 1999;Venkatasubbarao et al, 2000;Maurice et al, 2001;Fukushima et al, 2003;Sakaguchi et al, 2005;Zhong et al, 2006), emerging data have also suggested that the expressions of viral proto-oncogenes and oncogenes are capable of inducing TGF-b resistance through blocking the functions of Smads (Datta and Bagchi, 1994;Hahm et al, 1999;Mori et al, 2001;Lee et al, 2002;Dowdy et al, 2003;He et al, 2003;Wang et al, 2008). In this study, we found that FOXG1 was overexpressed in ovarian cancer cell lines and tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, decreased expressions or mutations in TGF-b R1, TGF-b RII and Smad4 have been frequently detected in a number of human cancers. (Eisma et al, 1996;Kim et al, 1996;Ko et al, 1998;Korchynskyi et al, 1999;Matsushita et al, 1999;Venkatasubbarao et al, 2000;Maurice et al, 2001;Paik et al, 2003;Sakaguchi et al, 2005;Perttu et al, 2006;Zhong et al, 2006).…”
mentioning
confidence: 99%
“…It is also noted, however, that tumor cells resist or do not respond to exogenous TGF-␤ possibly by having lower levels or mutated TGF-␤ receptors. 37,38 TGF-␤ derived from tumor cells could become a positive growth factor by stimulating the growth of fibroblastic cells around them to create a physical barrier, thus protecting the tumor cells from toxic stimuli, immuno-surveillance and even inhibiting the growth of normal cells (epithelial or immune cells) in the immediate vicinity of the tumor. 39 Hence, tumor cells bypass the propensity to succumb to growth inhibition by TGF-␤ (endogenously and exogenously produced), instead the tumor cells respond oppositely and possibly use endogenously and exogenously produced TGF-␤ as a positive growth factor, hence changing the functionality of TGF-␤ during carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%